Investigating the Turing Conditions for Diffusion-Driven Instability in Predator-Prey System with Hunting Cooperation Functional Response (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we focus on stability analysis of steady-state solutions of a predator-prey system with hunting cooperation functional response.The results show that the Turing instability can be affected not only the existence of hunting cooperation, but also the diffusion coefficients: (1) in theabsence of predator diffusion, diffusion-driven instability can be induced byhunting cooperation, but no stable patterns appear; (2) the system can occurdiffusion-driven instability and Turing patterns, when both predator and preyhave diffusion, and the diffusion coefficient of prey is greater than that of thepredator. The numerical simulations of two cases are presented to verify thevalidity of our theoretical results.